Predictors of sexual abstinence knowledge and attitude among in-school adolescents in South-West, Nigeria (2017)
This study investigated the influence of some demographic variables on the knowledge of and attitude towards sexual abstinence among in-school adolescents in South-West Nigeria. A descriptive survey research design was adopted for the study. Three hundred respondents comprising of 151 males and 149 females were randomly selected from six secondary schools in south-west Nigeria. Five research instruments were used to measure; sexual abstinence knowledge and attitude scale (0.84 & 0.63); self-esteem scale (0.77) religious orientation measure (0.73); general self-efficacy scale (0.80); sexual abstinence self-efficacy scale (0.79) and parent-adolescent communication scale (0.90). Six research questions. Data were analyzed at 0.05 level of significance using Pearson Product Moment Correlation (PPMC) and Multiple Regression analysis. The findings revealed that self-efficacy- (r = .370**, p(j000) <.01); sexual abstinence self-efficacy- (r = .449**, p(.000)<.01); parent- adolescent communication- (r = .233**, p(.000)<.01) and religiosity- (r = .135*, p(.020)<.05) correlated positively and significantly with knowledge of sexual abstinence; Also, self- efficacy, (r = .360**, p (.000) <.01), sexual abstinence self-efficacy (r = .411**, p(.000) <.01), parent-adolescent communication (r = .411**, p(.000) <.01) and religiosity (r = .158**, p(.006) <.05) showed positive and significant correlation with attitude towards sexual abstinence. Furthermore, all the variables jointly accounted for 34.9% variance in the prediction of sexual abstinence knowledge; and 43.0% variance in the prediction of attitude towards sexual abstinence. Based on the findings of this study, programmes promoting sexual abstinence should be organized more in worship centres so as to increase sensitization and awareness